Radiation Damage Mechanisms of Chemotherapeutically Active Nitroimidazole Derived Compounds - Chiarinelli, Jacopo; Casavola, Anna Rita; Castrovilli, Mattea Carmen; Bolognesi, Paola; Cartoni, Antonella; Wang, Feng; Richter, R.; Catone, Daniele; Tosic, Sanja; Marinkovic, Bratislav P.; Avaldi, Lorenzo (Frontiers in Chemistry, 2019)
Photoionization mass spectrometry, photoelectron-photoion coincidence spectroscopic technique and computational methods have been combined to investigate the fragmentation of two nitroimidazole derived compounds: the metronidazole and misonidazole. These molecules are used in radiotherapy thanks to their capability to sensitize hypoxic tumor cells to radiation by ‘mimicking’ the effects of the presence of oxygen as a damaging agent. Previous investigations of the fragmentation patterns of the nitroimidazole isomers (Bolognesi et al., 2016, Cartoni et al., 2018) have shown their capacity to produce reactive molecular species such as nitric oxide, carbon monoxide or hydrogen cyanide and their potential impact on the biological system. The results of the present work suggest that different mechanisms are active for the more complex metronidazole and misonidazole molecules. The release of nitric oxide is hampered by the efficient formation of nitrous acid or nitrogen dioxide. Although both metronidazole and misonidazole contain imidazole ring in the backbone, the side branches of these molecules lead to very different bonding mechanisms and properties.